P-039 Intravascular ultrasound of flow diverters in aneurysm treatment. (22nd July 2019) - Nicholson, A; Taylor, S; Woods, C; Cuoco, J; Klein, B; Guilliams, E; Marvin, E; Entwistle, J
Abstract : Introduction/Purpose: The use of flow diverting stents for the treatment of cerebral aneurysms has significantly increased since the PUFS (Pipeline for Uncoilable of Failed Aneurysms) trial was released in 2013. Based on the extensive literature on flow diverting stents one of the most critical features of stent placement is vessel wall apposition. Examining the cardiology literature, stents placed using intravascular ultrasound (IVUS) show a 50% decreased in-hospital mortality and a 34% decrease in major adverse cardiac events in the 24 months following stent placement. Although the degree of flow diversion and wall apposition in cerebral aneurysm treatments can be assessed on angiography, it often provides an incomplete picture, which can result in the unnecessary placement of multiple overlapping stents. In this study, we assess the utility and feasibility of intravascular ultrasound (IVUS) in determining wall apposition and quantifying flow diversion post stent placement. Materials and methods: Five (5) consecutive patients were selected who underwent angiography with possible flow diverting stent placement for known unruptured cerebral aneurysms at our institution. All five patients underwent full diagnostic angiography, followed by a separate endovascular surgery using flow diverting stents. Prior to stent placement, a Visions PV 0.014P RX (Philips) was introduced through the intermediate catheter past the aneurysm and a pullback recording was performed using Chromaflow for analysis. A Pipeline Flex Embolization Device (Medtronic) was then placed in the standard fashion. After stent placement, the IVUS catheter was re-introduced and another pullback recording obtained. Pre- and post- stent vessel diameter, as well as wall apposition was assessed. Flow diversion was assessed using Chromaflow power Doppler measurements. Results: Intravascular ultrasound was safe and technically feasible in 100% (5/5) of the patients analyzed. Vessel wall dimensions were compared to angiography in these patients, and the IVUS measurements influenced a change in stent size in 60% (3/5) patients. Likewise, Doppler flow measurements influenced the decision to not place additional stents in 60% of patients. Doppler flow decreased in the aneurysms by 60–100% after flow diversion, and 90–100% at the conclusion of the procedure. Follow up angiography at 3- and/or 6-months post stenting was obtained in 4 of our patients. Conclusion: Intravascular ultrasound is a safe and effective tool in the evaluation and treatment of cerebral aneurysms using flow diverting stents. In our small study our use of this technology improved accuracy of device sizing, wall apposition, and decreases the number of stents need to treat aneurysms. Disclosures: A. Nicholson: None. S. Taylor: None. C. Woods: None. J. Cuoco: None. B. Klein: None. E. Guilliams: None. E. Marvin: None. J. Entwistle: None.